INTERRELATION OF TECHNOLOGY AND IDEOLOGY IN INFORMAL SECOND LANGUAGE ACQUISITION: A TRANSDISCIPLINARY FRAMEWORK - Justsinta Sindi Alivi; Wiwik Mardiana (PARADIGM: Journal of Language and Literary Studies, 2020)
Technology in informal language learning is inevitably in this digital era since it offers opportunities and brings positive impacts on English language learners. Some related studies are concerned with a particular approach. Therefore, this study looks at a broader lens to investigate individuals' differences in developing a second language, and to what extent technology contributes to their second language acquisition by employing the transdisciplinary framework of Douglas Fir Group (2016). This case study involved two participants, and the data was collected through semi-structured interviews. The findings indicate that individual differences in learning English are influenced by social interaction (micro), environment (meso), and belief (macro). Technology is utilized not only as a medium of learning English but also as an identity construction. How ideology and technology are interrelated is further discussed.